Problems and perspectives of teacher education in foreign countries and in Lithuania - Petrauskaitė, Ramutė; Kučinskas, Vytolis (Acta Paedagogica Vilnensia, 1998)
The comparative analysis of the works of foreign education scientists (T. Sander, C. Evertson, M. Zlotnik and others) shows that there are many similarities in teacher education problems abroad and in Lithuania. We can mention such problems as not clearly defined the criterion of the selection of candidates to teacher education programmes; lack of integration between pedagogical theory and practice; too little effort to teach the future teachers to teach effectively and use modern teaching techniques; the role of practice work in teacher education is often overestimated or underestimated; teacher unemployment; lack of society concern for teacher education, work and living problems, etc. It is suggested to take on a systematic view for solving manifold and complicated problems of modern teacher education in Lithuania. It would be useful to coordinate all the levels of the teacher education and the research activities in the country. The universities and higher pedagogical schools should after the teacher education programmes extending possibilities of the students to have complementary course or requalify to other professions in cases of the unemployment. Lack of the teacher education ideology and policy is emphasized in the article.